Peran Current Ratio dalam Memoderasi Pengaruh Debt to Equity Ratio Terhadap Return on Equity pada Bank Syariah Indonesia - Lestari, Putri Sri; Barokah, Bella Yuliawan; Setiawan, Iwan (Universitas Islam Lamongan, 2024)
As the fastest growing banking companies, Bank Syariah Indonesia needs to monitor financial ratios, such as current ratio (CR) and debt to equity ratio (DER) to measure financial performance and stability. This research focuses on how the CR affects the relationship between DER and RoE to provides an overview of the capital structure and liquidity policies that affect the profitability of Islamic banks. This research uses a quantitative descriptive method with secondary data on time series from 2021 to 2023, taken from the financial statements of PT. Bank Syariah Indonesia Tbk. Data processing is carried out with SPSS version 26, involving regression analysis, coefficient of determination, and hypothesis testing. To test the hypothesis, this study applied Moderated Regression Analysis (MRA) to multiple linear regression, with moderation variables to regulate the interaction between independent and dependent variables. This research shows that in Bank Syariah Indonesia, there is no significant correlation between DER and RoE. That is, high DER does not necessarily mean greater profitability. This has an impact on management decisions related to capital structure and investment. In addition, the CR does not have a significant impact on the relationship between DER and RoE, indicating that moderation by CR does not allow revenue optimization.